THE ETHICS OF EMOTION IN AI SYSTEMS - Stark, Luke; Hoey, Jesse (AoIR Selected Papers of Internet Research, 2019)
Computational analyses of data pertaining to human emotional expression have a surprisingly long history and an increasingly critical role in social machine learning (ML) and artificial intelligence (AI) applications. Contemporary, quotidian, narrow AI/ML technologies are most frequently used by social media platforms for modeling and predicting human emotional expression as signals of interpersonal interaction and personal preference. Yet while the ethical and social impacts of ML/AI systems have of late become major topics of both public discussion and academic debate , the ethical dimensions of AI/ML analytics for emotional expression have been under-theorized in these conversations. In this paper, we connect contemporary technical methods for analyzing emotional expression via AI/ML with extant problems in the ethics of AI discourse, in doing so highlighting tensions within that broader discourse and implications for the application of emotion analysis in practice.